2020
DOI: 10.1111/eos.12695
|View full text |Cite
|
Sign up to set email alerts
|

Oral health literacy, self‐rated oral health, and oral health‐related quality of life in Brazilian adults

Abstract: Oral health literacy, self-rated oral health, and oral health-related quality of life in Brazilian adults Bado FMR, De Checchi MHR, Cortellazzi KL, Ju X, Jamieson L, Mialhe FL. Oral health literacy, self-rated oral health, and oral health-related quality of life in Brazilian adults. Eur J Oral Sci 2020; 128: 218-225. © 2020 Eur J Oral SciThe aim of this study was to investigate associations between oral health literacy (OHL), self-rated oral health (SROH), and oral health-related quality of life (OHR-QoL) in B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
27
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 54 publications
(81 reference statements)
5
27
4
Order By: Relevance
“…So, the first null hypothesis was accepted. In contrast to this study, Bado et al 18 reported the association between OHL and OHRQoL at Brazilian adults. Besides this, Divaris et al investigated that "low" OHL level individuals showed significantly more "Oral Health Related Quality of Life" impacts versus those with higher literacy.…”
Section: Discussioncontrasting
confidence: 94%
See 1 more Smart Citation
“…So, the first null hypothesis was accepted. In contrast to this study, Bado et al 18 reported the association between OHL and OHRQoL at Brazilian adults. Besides this, Divaris et al investigated that "low" OHL level individuals showed significantly more "Oral Health Related Quality of Life" impacts versus those with higher literacy.…”
Section: Discussioncontrasting
confidence: 94%
“…19 In a previous study Jamieson et al 20 reported a significant inverse interaction between OHL and OHRQoL among American Indians but not among Indigenous Australians between 17-72 yearsold. In our study, participants in different races were not evaluated and in contrast to findings of Divaris et al 19 and Bado et al 18 there was no significant association was found between OHL and OHRQoL.…”
Section: Discussioncontrasting
confidence: 93%
“…[32][33][34][35] Similar to our findings, previous studies indicate that income and self-rated oral health are important predictors of dental service utilization. 12,36,37 In the past two decades, several instruments have been developed to measure population and individual levels of OHL. Nonetheless, the vast majority of these tools are exclusively focused on word recognition, ignoring the important dimensions of OHL.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 Studies have shown that individuals with low levels of OHL, present higher prevalence rates of oral conditions, such as dental caries, missing teeth, and periodontal disease, in addition to worse self-rated oral health, irregular attendance to dental appointments, poor oral healthrelated quality of life, and greater deleterious oral habits. [6][7][8][9][10][11][12] However, evidence from systematic reviews indicates inconclusive findings regarding these associations. [13][14][15] Furthermore, OHL is a construct that influences the use of dental services.…”
Section: Introductionmentioning
confidence: 99%
“…Taken together, the two OHIP-14 scores mentioned above demonstrate a higher impact on oral health conditions in people with mental illness than in the general adult population in Brazil [19,[28][29][30][31][32][33] and worldwide [25,26,[34][35][36][37], a fact that should draw managers' attention to actions directed toward this group. In spite of other tools being applied to investigate OHRQoL in people with depression and/or schizophrenia, such as the Geriatric Oral Health Assessment Index (GOHAI) [38,39], OHIP-14 has been the instrument most widely used to measure OHRQoL in the adult general population and among patients with mental illness [11,12,[14][15][16][17]40].…”
Section: Discussionmentioning
confidence: 99%